2010
DOI: 10.1021/ac902694d
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Based Detection of Chemical Warfare Agent Mimics Using Ferrocene-Lysine Modified Carbon Nanotubes

Abstract: A recognition layer formed by multiwalled carbon nanotubes (MWCNTs) covalently modified with a ferrocene-lysine conjugate deposited on the indium tin oxide (ITO) was investigated as a sensor for chemical warfare agent (CWA) mimics. Electrochemical impedance spectroscopy measurements showed that upon addition of CWA mimic dramatic changes occurred in the electrical properties of the recognition layer. These changes allowed the detection of nerve agent analogues at the micromolar level, and a limited sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…This finding was not surprising considering the potential composition, topography (Figure 4), and limited response (Figure 6) observed with electrodes fabricated from both imaging card paper and multipurpose printing paper. For the case of electrodes fabricated from 3MM chromatography paper, the obtained spectra was fitted with a Randles-type equivalent electrical circuit (see insert in Figure 8B), containing elements representing the resistance of the solution ( R sol = 46.6 ± 0.4 Ω), the internal resistance of the film ( R film = 2.6 ± 0.1 Ω), the capacitance of the film ( C film = 22 ± 1 μF), the charge transfer resistance ( R ct = 63 ± 2 kΩ), and surface constant phase element (CPE= 32 ± 2 μF) with an exponent constant (α = 0.93, instead of the traditional C dl representing the capacitance of the double layer) to account for heterogeneities and roughness of the surface of the electrode [62-64]. These results that are in within the range reported for other carbon electrodes [37, 41, 65] suggest that the electrochemical process is limited by the RCT rather than the internal resistance of the films.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was not surprising considering the potential composition, topography (Figure 4), and limited response (Figure 6) observed with electrodes fabricated from both imaging card paper and multipurpose printing paper. For the case of electrodes fabricated from 3MM chromatography paper, the obtained spectra was fitted with a Randles-type equivalent electrical circuit (see insert in Figure 8B), containing elements representing the resistance of the solution ( R sol = 46.6 ± 0.4 Ω), the internal resistance of the film ( R film = 2.6 ± 0.1 Ω), the capacitance of the film ( C film = 22 ± 1 μF), the charge transfer resistance ( R ct = 63 ± 2 kΩ), and surface constant phase element (CPE= 32 ± 2 μF) with an exponent constant (α = 0.93, instead of the traditional C dl representing the capacitance of the double layer) to account for heterogeneities and roughness of the surface of the electrode [62-64]. These results that are in within the range reported for other carbon electrodes [37, 41, 65] suggest that the electrochemical process is limited by the RCT rather than the internal resistance of the films.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that the R film decreased around a 96% respect to the resistance value displayed by the blank (bare CE), in agreement with the hypothesis that the conductivity is favored by the metallic properties of the nanoparticles. It was also observed that the electric double-layer capacitance (fitted using a CPE dl to represent the deviation from the ideal comportment) showed a slight increase with respect to the bare electrodes, observation that can be attributed to heterogeneities and roughness in the electrode surface [47-49] and that correlate well to the presence of CuNPs on the surface of the carbon fibers. In agreement with features observed in the SEM micrograph (Figure 2), the lower exponent values obtained for both substrates (α CPE dl < 0.5) [45] suggest that they behave as porous electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Nanostructured materials, which are very attractive due to their unique optical, electrical, catalytic, and magnetic properties, have been applied in the field of biosensors and nanoelectronic devices. In recent years, the electrochemical immunoassays have been developed based on nanomaterials, such as colloid gold (Xiao & Yu, 2010), nano-SiO 2 (Tang, Su, Tang, Ren & Chen, 2010;Wu, Chen & Liu, 2009), nano-TiO 2 (Wang, Ruan, Kanayeva, Lassiter & Li, 2008), nano-Ag (Loyprasert et al, 2008), carbon nanotube (Diakowski, Xiao, Petryk & Kraatz, 2010), Fe 3 O 4 nanoparticles (Huang et al, 2010), and nano-Pt (Huang, Wen, Jiang, Shen & Yu, 2008), all of which have attracted considerable interest in biosensor development. Among the nanomaterials mentioned above, gold nanoparticles, which have good characteristics of easy preparation, good biocompatibility and relatively large surface, are widely used to immobilize DNA (Li, Feng, Dong & Tang, 2010;Zhang, Wang & Xu, 2010), cell (Yan, Chen & Ju, 2007), cytochrome (Bonk & Lisdat, 2009;Li et al, 2009), and enzyme (Kim, Kang, Shim & Moon, 2008;Wang, Wang, Di & Tu, 2008) in the field of biological studies.…”
Section: Introductionmentioning
confidence: 99%